DEVELOPMENT OF MANAGEMENT ACCOUNTING RESEARCH IN INDONESIA: A BIBLIOGRAPHY STUDY - Sintia Farach Dhiba; Dianne Frisko Koan (Jurnal Aplikasi Akuntansi, 2023)
This paper reviews the current state of management accounting research to assess the structure of the research field and track the growing literature of Indonesian researchers. A bibliography study is used to review 244 papers in the field of management accounting published in Indonesia's top national accounting journals over the past 20 years. The study tabulates the topic, research method, and settings utilizing spreadsheet and qualitative data analytics software, Nvivo 12. Management accounting research in Indonesia represents a small portion of the broader accounting field study. This study gives information on which journal produces most accounting management research and which journal favors certain research methods. Most research concentrates more on budgeting and performance-determinant analysis. The quantitative research method dominates the study, with the survey instrument serving to answer the research question. Most research is conducted in the public sector, making the public sector and management accounting research have a high intersection. This study's findings hold implications for management accounting scholars to provide insights into identifying research gaps and novelties for further research